2018
DOI: 10.1371/journal.pone.0204250
|View full text |Cite
|
Sign up to set email alerts
|

AIF-1 gene does not confer susceptibility to Behçet’s disease: Analysis of extended haplotypes in Sardinian population

Abstract: BackgroundBehçet’s disease (BD) is a polygenic immune-mediated disorder characterized by a close association with the HLA-B*51 allele. The HLA region has a strong linkage disequilibrium (LD) and carries several genetic variants (e.g. MIC-A, TNF-α genes) identified as associated to BD because of their LD with HLA-B*51. In fact, the HLA-B*51 is inherited as part of extended HLA haplotypes which are well preserved in patients with BD. Sardinian population is highly differentiated from other Mediterranean populati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 24 publications
0
2
1
Order By: Relevance
“…The BODI study was conducted on 228 patients from 10 southern European centers with a male : female ratio of 0.97:1. Moreover, a recent study from Cagliari, Italy reported a male : female ratio of 0.5:1, 20 while in this study the male : female ratio was 2.6:1. Furthermore, a possible cultural reluctance among women from Eastern countries to visit a physician for genital ulcers leading to delayed diagnosis of BD with the development of more severe organ involvement may partly serve as another cause.…”
Section: Discussioncontrasting
confidence: 61%
“…The BODI study was conducted on 228 patients from 10 southern European centers with a male : female ratio of 0.97:1. Moreover, a recent study from Cagliari, Italy reported a male : female ratio of 0.5:1, 20 while in this study the male : female ratio was 2.6:1. Furthermore, a possible cultural reluctance among women from Eastern countries to visit a physician for genital ulcers leading to delayed diagnosis of BD with the development of more severe organ involvement may partly serve as another cause.…”
Section: Discussioncontrasting
confidence: 61%
“…In absence of universally accepted diagnostic laboratory test, the diagnosis can only be made based on clinical symptoms and signs [1][2][3]. Patients with BD share some common features with autoimmune and autoinflammatory diseases [4][5][6][7][8]. The prevalence of BD is higher in the ancient silk route areas-geographically the Mediterranean and the Middle East regions (between the latitudes of 30˚N and 45˚N) [9,10] with an estimated worldwide prevalence of 10.3/100,000 and is equally distributed in men and women [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…The etiology of BS remains unknown, although the most widely held pathogenic hypothesis is that of aberrant autoinflammatory response triggered by an environmental agent in genetically susceptible subjects 2,3. Supporting this is the geoepidemiology of the disease and the association with polymorphisms in the HLA complex, particularly the HLA-B*51 4–6…”
Section: Introductionmentioning
confidence: 99%